Kinematic comparisons of the Tsukahara vault between a top-level athlete and sublevel collegiate athletes - Park, C.-H.; Kim, Y.-K.; Back, C.-Y. (Korean Journal of Sport Biomechanics, 2016)
Objective: The purpose of this study was to investigate kinematic comparisons of Tsukahara vault in gymnastics between a top-level athlete and sublevel collegiate athletes in order to obtain information on key biomechanical points for successful Tsukahara vaults. Methods: An Olympic gold medalist (height, 160 cm; weight, 52 kg; age, 25 years) and five sublevel collegiate gymnasts (height, 168.2 ± 3.4 cm; weight, 59.6 ± 3.1 kg; age, 23.2 ± 1.6 years) participated in this study. They repeatedly performed Tsukahara vaults including one somersault. Fourteen motion-capturing cameras were used to collect the trajectories of 26 body markers during Tsukahara vaults. Event time, displacement and velocity of the center of mass, joint angles, the distance between the two hands on the horse, and averaged horizontal and vertical impact forces were calculated and compared. Results: The top-level athlete showed a larger range of motion (ROM) of the hip and knee joints compared to sublevel collegiate athletes during board contact. During horse contact, the top-level athlete had a narrow distance between the two hands with extended elbows and shoulders in order to produce a strong blocking force from the horse with a shorter contact time. At the moment of horse take-off, reactive hip extension of the top-level athlete enhanced propulsive take-off velocity and hip posture during post-flight phase. Conclusion: Even though a high velocity of the center of mass is important, the posture and interactive action during horse contact is crucial to post-flight performance and the advanced performance of Tsukahara vaults.